Post-polymerization functionalization of epoxide-containing copolymers in trifluoroethanol for synthesis of polymer-drug conjugates. (2nd September 2016) - Li, Shaohua; Cohen-Karni, Devora; Kallick, Ethan; Edington, Howard; Averick, Saadyah
Abstract: Post-polymerization functionalization is a critical tool in preparing functional materials. The critical aspects of post-polymerization reactions are high yields, short reaction times, simple purification, near stoichiometric amounts of reactants, and facile reaction conditions. Polymeric epoxides (i.e. poly(glycidyl methacrylate)) represent an underutilized class of functionalized polymers due to long reaction times, high temperatures, and large excess of reactants to drive the reaction to high conversion in a reasonable time frame. In this manuscript we describe the use of a novel solvent trifluoroethanol (TFE) for the ring opening of amines with poly(glycidyl methacrylate). We demonstrate that TFE gives faster reaction times and higher yields than traditional solvents used for the ring opening reaction. We utilized TFE to prepare dual functionalized polymers that could be "clicked" using strain promoted azide alkyne cycloaddition and an amine-bearing drug ring opening of the polymeric backbone. Graphical abstract: Highlights: Trifluoroethanol was used a solvent in the ring opening reaction of amines with epoxides. Ring opening reactions carried out in TFE had faster reaction times and better yields compared to DMSO. The antibiotic ciprofloxacin was reacted with the pGMA polymer in TFE.